Risk Factors for Recurrence of Intracranial Aneurysm After Coil Embolization: A Meta-Analysis - Jin, Ji; Guo, Geng; Ren, Yeqing; Yang, Biao; Wu, Yongqiang; Wang, Shule; Sun, Yanqi; Wang, Xiaogang; Wang, Yuxiao; Zheng, Jianzhong (Frontiers in Neurology, 2022)
Intracranial aneurysm is a severe cerebral disorder involving complicated risk factors and endovascular coiling is a common therapeutic selection for intracranial aneurysm. The recurrence is a clinical challenge in intracranial aneurysms after coil embolization. With this study, we provided a meta-analysis of the risk factors for the recurrence of intracranial aneurysm after coil embolization. Nine studies were included with a total of 1,270 studies that were retrieved from the database. The sample size of patients with intracranial aneurysms ranged from 241 to 3,530, and a total of 9,532 patients were included in the present meta-analysis. The intracranial aneurysms that occurred in middle cerebral artery (MCA) (OR = 1.09, 95% CI: 1.03–1.16, P = 0.0045) and posterior circulation (OR = 2.01, 95% CI: 1.55–2.60, P = 0.000) presented the significantly higher risk of recurrence after coil embolization. Meanwhile, intracranial aneurysms of size > 7 mm (OR = 5.38, 95%CI: 3.76–7.70, P = 0.000) had a significantly higher risk of recurrence after coil embolization. Moreover, ruptured aneurysm (OR = 2.86, 95% CI: 2.02–4.04, P = 0.000) and subarachnoid hemorrhage (SAH) (OR = 1.57, 95% CI: 1.20–2.06, P = 0.001) was positively correlated with the risk of recurrence after coil embolization. In conclusion, this meta-analysis identified the characteristics of intracranial aneurysms with MCA, posterior circulation, size > 7 mm, ruptured aneurysm, and SAH as the risk factors of recurrence after coil embolization for intracranial aneurysms.